Cloning, characterization and anion inhibition study of a β-class carbonic anhydrase from the caries producing pathogen Streptococcus mutans. Issue 13 (1st July 2015) - Dedeoglu, Nurcan; De Luca, Viviana; Isik, Semra; Yildirim, Hatice; Kockar, Feray; Capasso, Clemente; Supuran, Claudiu T.
Graphical abstract: Abstract: The oral pathogenic bacterium involved in human dental caries formation Streptococcus mutans, encodes for two carbonic anhydrase (CA, EC 4.2.1.1) one belonging to the α- and the other one to the β-class. This last enzyme (SmuCA) has been cloned, characterized and investigated for its inhibition profile with a major class of CA inhibitors, the inorganic anions. Here we show that SmuCA has a good catalytic activity for the CO2 hydration reaction, with k cat 4.2 × 10 5  s −1 and k cat / K m of 5.8 × 10 7  M −1  × s −1, being inhibited by cyanate, carbonate, stannate, divannadate and diethyldithiocarbamate in the submillimolar range ( K I s of 0.30–0.64 mM) and more efficiently by sulfamide, sulfamate, phenylboronic acid and phenylarsonic acid ( K I s of 15–46 μM). The anion inhibition profile of the S. mutans enzyme is very different from other α- and β-CAs investigated earlier. Identification of effective inhibitors of this new enzyme may lead to pharmacological tools useful for understanding the role of S. mutans CAs in dental caries formation, and eventually the development of pharmacological agents with a new mechanism of antibacterial action.